Imaging modalities for cardiovascular phenotyping in asymptomatic people living with HIV. (June 2021) - Bonou, Maria; Kapelios, Chris J; Athanasiadi, Eleni; Mavrogeni, Sophie I; Psichogiou, Mina; Barbetseas, John
Cardiovascular disease (CVD) has emerged as a leading cause of non-HIV-related mortality among people living with HIV (PLWH). Despite the growing CVD burden in PLWH, there is concern that general population risk score models may underestimate CVD risk in these patients. Imaging modalities have received mounting attention lately to better understand the pathophysiology of subclinical CVD and provide improved risk assessment in this population. To date, traditional and well-established techniques such as echocardiography, pulse wave velocity, and carotid intima thickness continue to be the basis for the diagnosis and subsequent monitoring of vascular atherosclerosis and heart failure. Furthermore, novel imaging tools such as cardiac computed tomography (CT) and cardiac CT angiography (CCTA), positron emission tomography/CT (PET/CT), and cardiac magnetic resonance (CMR) have provided new insights into accelerated cardiovascular abnormalities in PLWH and are currently evaluated with regards to their potential to improve risk stratification.